Outcome and toxicity assessment of feline small cell lymphoma: 56 cases (2000–2010). Issue 2 (29th October 2015) - Pope, Kendra V.; Tun, Alex E.; McNeill, Conor J.; Brown, Dorothy C.; Krick, Erika L.
Abstract: Feline small cell lymphoma is associated with greater response to treatment and survival when compared to large cell lymphoma. Treatment‐associated toxicity, response to rescue chemotherapy and prognostic factors are largely unknown. This retrospective study was performed to identify treatment‐associated toxicity, response to rescue chemotherapy and treatment outcome for cats diagnosed with small cell lymphoma of various anatomic locations. Medical records from 56 cats were evaluated. All cats were treated with glucocorticoid and chlorambucil with discontinuation of treatment recommended at 1 year if complete clinical response was documented. Chemotherapy toxicity was uncommon (33.9%) and generally mild. Grade III or IV hepatotoxicity was documented in 10.7% of patients. Overall response rate was 85.7% with glucocorticoid and chlorambucil. Median progression‐free survival was 1078 days. Overall response rate for rescue chemotherapy was 59%. Reintroduction of prednisone and chlorambucil was associated with significantly longer survival than prednisone and lomustine (>1500 vs. 492 days, P  = 0.01). Median overall survival times for cats with lymphoma of the gastrointestinal tract was not significantly different from those with extra‐intestinal disease locations (1148 vs. 1375 days, P  = 0.23). Median overall survival was 1317 days. Toxicity, other than hepatotoxicity was mild. Rescue chemotherapy with re‐introduction of glucocorticoids and chlorambucil was most successful. Discontinuation of glucocorticoid and chlorambucil with subsequent reintroduction as rescue chemotherapy appears to be just as effective as continued administration in cats. Abstract : Feline small cell lymphoma is associated with greater response to treatment and survival when compared with large cell lymphoma, however, treatment‐related toxicity and response to rescue chemotherapy are less well established. Fifty‐six cases were retrospectively evaluated and provided information regarding treatment‐related outcomes, hepatotoxicity associated with chlorambucil chemotherapy and favourable response rates with reintroduction of first‐line chemotherapy agents at the time of disease progression.